Campus Governance in U.S. Universities and Colleges - Laforge, William N. (Review of European and Comparative Law, 2020)
The governance of universities and colleges in the United States basically follows the concept and spirit of democracy embraced by the nation from its birth. The systems and practices in place at most U.S. institutions of higher learning include collaborative, representative, or collective decision-making arrangements known as shared governance. However, these systems and practices are hardly uniform due to the diversity of governance patterns that reflect the unique and different history, needs, and mission of a particular institution. Sometimes they are differentiated from, and contrasted with, corporate, business, and more authoritarian or centralized forms of institutional governance. In contrast with university governance elsewhere in the world—that can range from strong central government control to private self-regulated operations—the U.S. forms of campus governance have emerged in a country that does not have centralized authority over education. U.S. institutions of higher learning respond to a variety of controls and interests that are on display variously at public, private non-profit, private for-profit, and religious universities. Governance, authority, and administration are spread across a wide spectrum of players, including governing boards; presidents, chancellors, and other administrators; the academy/faculty; administrative staff; campus committees; students; and, even some external factors. Shared governance is not a perfect formula or panacea for university administration and decision-making. It does, however, provide a methodology, system, and concept that can help guide the leadership of a university as it approaches the administration and conduct of its educational responsibilities. In today’s higher education environment, the term governance is rather expansive. In one sense, it means top-down governance that is the rightful role and authority of an institutional board charged with overseeing policy, programming, performance, and executive guidance and evaluation. But, it also variously means the use of institutional strategies, operations, and components to distribute, disseminate, and “share” authority and responsibilities for a university’s administrative, management, and decision-making functions, i.e., “on-campus governance.” In this respect, shared governance “borrows” many of the attributes and principles of democratic government. In any case, shared governance, in its many forms and applications, is widely practiced in U.S. universities, including Delta State University.